ADVANCES IN SMART FACTORY AUTOMATION: INTEGRATING ROBOTICS, IOT, AND CYBER-PHYSICAL SYSTEMS - Gupta, Sandeep (Journal of Global Research in Mathematical Archives(JGRMA), 2025)
Industry 4.0 sees the modern manufacturing being transformed due to the combination of automation and robotics, Internet of Things (IoT), Cyber-Physical Systems (CPS), and artificial intelligence (AI). The present paper gives a detailed view of how all these technologies together ensure smart factories through improved efficiency in operations, quality of products, and real-time decision-making. Automation and AI-based analytics are able to optimize production processes, whereas advanced robotics and human-robot collaboration enhance flexibility, safety, and precision of tasks. IoT and CPS provide a continuous connection between physical objects and computerized systems, which contribute to the massive data collection and monitoring and prediction regulating control. The Digital Twin technology also enhances the process simulation, lifecycle optimization, and intelligent manufacturing management. By combining insights into recent developments, applications, and technological trends, the present paper demonstrates that the digital transformation is crucial in the formation of future manufacturing ecosystems and outlines the essential issues and research opportunities to apply smart manufacturing industrial automation in the future. Keywords: Automation, Smart Factories, Industry 4.0, Robotics, IoT, Cyber-Physical Systems (CPS), IIoT, Edge Computing.